1999
DOI: 10.1037/h0080422
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of psychotherapy by lesbians, gay men, and bisexuals: Findings from a nationwide survey.

Abstract: Based on a survey of the psychotherapy histories of 600 lesbians, gay men, and bisexuals, the number, duration, and circumstances of each therapy episode, and respondents' views of their therapists and of therapy, are reported. Findings suggest that lesbians and gay men are among the most active and satisfied--but least acknowledged--consumers of psychotherapy. Routine inclusion of sexual orientation as a demographic variable in mental health services research is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 29 publications
(24 reference statements)
2
45
1
2
Order By: Relevance
“…The present study revealed that counselors disclosing homosexual as opposed to heterosexual orientation were perceived as significantly more attractive. These findings are consistent with research demonstrating an increased tendency for LGB clients to choose counselors of a similar sexual orientation (Jones & Gabriel, 1999). However, it is important to note that despite such initial preference, research has also found that sexual orientation is perceived as less important than counselor competence by LGB clients (Saulnier, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…The present study revealed that counselors disclosing homosexual as opposed to heterosexual orientation were perceived as significantly more attractive. These findings are consistent with research demonstrating an increased tendency for LGB clients to choose counselors of a similar sexual orientation (Jones & Gabriel, 1999). However, it is important to note that despite such initial preference, research has also found that sexual orientation is perceived as less important than counselor competence by LGB clients (Saulnier, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…While loneliness was the reason for having sought counseling 48.4% of the time, sexual orientation-related issues accounted for help-seeking 71% of the time. This figure is higher than findings presented in other research included in this review (see Jones & Gabriel, 1999;Mapou, Ayres, & Cole, 1983;Sorensen & Roberts, 1997). More than a quarter of the participants (25.8%) felt as though their sexual orientation was a problem in receiving or for remaining in counseling.…”
Section: Reviewcontrasting
confidence: 73%
“…Certainly the rates of prior and current counseling were high (over 75%) for all three groups. Prior research (Jones & Gabriel, 1999;Morgan, 1992;Morgan & Eliason, 1992) has found lesbians to seek psychotherapy at much higher rates than heterosexual women. For example, Morgan (1992) found 77.5% of lesbians and 28.9% of heterosexual women to have ever been in therapy; comparable rates in the study by Rothblum and Factor (2001) were 72.3% for lesbians and 54.9% for their heterosexual sisters.…”
Section: Stressors and Protective Factors For Lesbian Mothersmentioning
confidence: 99%